2010
DOI: 10.1186/1745-6150-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a Quorum Sensing mechanism triggers tumorigenesis: a simple discrete model corroborated by experiments in mammary cancer stem cells

Abstract: BackgroundThe balance between self-renewal and differentiation of stem cells is expected to be tightly controlled in order to maintain tissue homeostasis throughout life, also in the face of environmental hazards. Theory, predicting that homeostasis is maintained by a negative feedback on stem cell proliferation, implies a Quorum Sensing mechanism in higher vertebrates.ResultsApplication of this theory to a cellular automata model of stem cell development in disrupted environments shows a sharply dichotomous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…Quorum sensing is a form of intercellular communication which allows unicellular prokaryotic organisms to respond synchronously to alterations in microenvironment, almost as if they were a multicellular organism [24, 25]. The involvement of quorum-sensing mechanisms in human tumor cell biology and metastasis has been hypothesized [26, 27]. …”
Section: Resultsmentioning
confidence: 99%
“…Quorum sensing is a form of intercellular communication which allows unicellular prokaryotic organisms to respond synchronously to alterations in microenvironment, almost as if they were a multicellular organism [24, 25]. The involvement of quorum-sensing mechanisms in human tumor cell biology and metastasis has been hypothesized [26, 27]. …”
Section: Resultsmentioning
confidence: 99%
“…Inter-cellular interactions effects are beyond strictly mechanical. Inter-cellular communication has been shown, for example, to maintain homeostasis in cells, where reduction of cell-cell signals could trigger stem cell immortalization and proliferation resulting in tumorigenesis (Agur et al, 2010). These studies reveal importance of the cell-cell interactions in developmental events such as differentiation, to expose dependence of pluripotent stem cells on their biophysical environment as they gain specificity and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a hypothesis that cancer cells may use a quorum-sensing mechanism to regulate multicellular functions and control steps in metastatic colonization has been proposed [33]. It has also been reported that disruption of a quorum-sensing mechanism triggers tumorigenesis in mammary cancer stem cells [34]. These studies indicate that computationally modeling self-organization using adaptive networks may lead to useful insights in diverse biological fields.…”
Section: Discussionmentioning
confidence: 99%